Evolution of Micron-Scale Pore Structure and Connectivity of Lignite during Pyrolysis. (10th April 2020) - Meng, Qiaorong; Zhao, Yangsheng; Kang, Zhiqin; Wang, Yong; Gao, Li; Zhang, Yongfeng
Abstract : Based on the high-precision microcomputed tomography (micro-CT) technology, the evolution of the μ m-scale pore structure and connectivity of lignite during pyrolysis from room temperature to 600°C was studied. The results show that the pore connectivity of lignite increases with the increase of temperature, and the change of pore structure can be divided into four stages: the first stage is from room temperature to 100°C, characterized by generation and connection of small-diameter pores. The second stage is 100–200°C, characterized by rapid expansion and interconnection of pores due to the thermal cracking. The third stage is from 200°C to 450°C, characterized by the slow evolution of pore structure for pyrolysis. The fourth stage is from 450°C to 600°C, characterized by pore interconnection for pyrolysis. 200°C is the temperature at which the μ m-scale pore structure of lignite changes dramatically. During the whole pyrolysis process from room temperature to 600°C, the pore quantity of lignite is mainly from the pores of a diameter of 0.65–3 μ m. At 200°C and above, the pore volume of lignite is mainly from the pores with a diameter larger than 100 μ m, but they are few. These research results have important theoretical reference values for the upgrading and pyrolysis of lignite.